2023
DOI: 10.1093/mnras/stad1341
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray spectroscopy study of structural stability of superhydrogenated pyrene derivatives

Abstract: The stability of polycyclic aromatic hydrocarbons (PAHs) upon soft X-ray absorption is of crucial relevance for PAH survival in X-ray dominated regions (XDRs). PAH stability depends on molecular size but also on the degree of hydrogenation that is related to H2 formation in the interstellar medium (ISM). In this project, we intend to reveal the changes of electronic structure caused by hydrogenation and the impact of hydrogenation on the stability of the carbon backbone for cationic pyrene and its hydrogenated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A number of recent experiments have been performed on pyrene cations [27][28][29][30] and on hydrogenated pyrene. 31,32 Lietard and Verlet 33 have applied photoelectron spectroscopy to study microhydration of pyrene anions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent experiments have been performed on pyrene cations [27][28][29][30] and on hydrogenated pyrene. 31,32 Lietard and Verlet 33 have applied photoelectron spectroscopy to study microhydration of pyrene anions.…”
Section: Introductionmentioning
confidence: 99%
“…Electron impact and electron attachment studies were performed in 2005 , in order to investigate ionic dissociation processes in glycolaldehyde. To the best of our knowledge, no previous experimental studies on the X-ray absorption or photoemission spectra of glycolaldehyde have been reported, despite the fact that they could be relevant in the context of X-ray astronomy, e.g., as reference data for astrophysical observations and/or in the study of X-ray photodesorption from interstellar ices. …”
Section: Introductionmentioning
confidence: 99%